2015
DOI: 10.1002/mus.24621
|View full text |Cite
|
Sign up to set email alerts
|

Muscle pathology grade for facioscapulohumeral muscular dystrophy biopsies

Abstract: Background As we move towards planning for clinical trials in Facioscapulohumeral Muscular Dystrophy (FSHD), a better understanding of the clinical relationship with morphological changes in FSHD muscle biopsies will be important for stratifying patients and understanding post-therapeutic changes in muscle. Methods We performed a prospective cross-sectional study of quadriceps muscle biopsies in 74 genetically confirmed FSHD participants (64 FSHD1, 10 FSHD2). We compared a 12-point muscle pathology grade to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 22 publications
(58 reference statements)
2
43
0
1
Order By: Relevance
“…Besides, our SHD patients had progressive limb weakness and muscle atrophy without facial involvement during follow-up, relatively excluded from pre-symptomatic states. The biopsies exhibited non-specific and mild myopathic changes including a small amount of inflammatory infiltration, consistent with the previous report in classical FSHD [18]. Extramuscular assessments covering pulmonary function and electrocardiogram were normal or mild.…”
Section: Discussionsupporting
confidence: 90%
“…Besides, our SHD patients had progressive limb weakness and muscle atrophy without facial involvement during follow-up, relatively excluded from pre-symptomatic states. The biopsies exhibited non-specific and mild myopathic changes including a small amount of inflammatory infiltration, consistent with the previous report in classical FSHD [18]. Extramuscular assessments covering pulmonary function and electrocardiogram were normal or mild.…”
Section: Discussionsupporting
confidence: 90%
“…Muscle biopsy typically demonstrates nonspecific myopathic changes, including fiber size variability, internalized nuclei, and fibrosis. Up to one third of patients have an inflammatory infiltrate composed of both CD4+ and CD8+ T cells that can lead to misdiagnosis as PM [42,43]. The infiltrate, which may be most prevalent in the early stages of the disease, appears patchy and varies widely in intensity between biopsy samples [44].…”
Section: Facioscapulohumeral Muscular Dystrophymentioning
confidence: 99%
“…In FSHD, muscles undergo structural changes as the disease progresses, including atrophy, fatty infiltration, edema, and fibrosis. These changes can all influence the impedance across the muscle tissue . In a previous cross‐sectional study on EIM in FSHD, we showed that EIM is a reliable measure of muscle composition in FSHD that correlates with functional outcome measures .…”
mentioning
confidence: 73%
“…These changes can all influence the impedance across the muscle tissue. 8,9 In a previous cross-sectional study on EIM in FSHD, we showed that EIM is a reliable measure of muscle composition in FSHD that correlates with functional outcome measures. 10 Studies on other neuromuscular disorders such as amyotrophic lateral sclerosis, congenital myopathies, and Duchenne muscular dystrophy have shown that EIM is able to capture changes over time, [11][12][13][14] although research is ongoing regarding what variables are most suitable to use in each different disorder.…”
Section: Facioscapulohumeral Muscular Dystrophy (Fshd)mentioning
confidence: 90%